Development and Characterization of Oral Disintegrating Tablet Containing Nanosuspension of Lurasidone Hydrochloride antipsychotic Drug - Kumar, Dr.Â R. Suresh (Asian Journal of Pharmaceutics (AJP), 2017)
Background: Lurasidone hydrochloride, is BCS Class II drug with poor bioavailability of about 7% and lacking solubility to show quick response. The aim of the work was to develop oral disintegrating tablet containing nanosuspension of Lurasidone Hydrochloride thereby improve the solubility and overcome the poor bioavailability. Material and Methods: Nanosuspension of Lurasidone hydrochloride was prepared by media milling technique. HPMC and poloxamer were used as stabilizers to prevent from surface charge agglomeration. Kollidon, Croscarmellose sodium and ludipress were used as super disintegrants. The nanosuspension was optimized by evaluating the particle size analysis, zeta potential, milling time and concentration of stabilizer. Results and Discussion: The particle size and zeta potential of F4 formulation were found to be 245.4 nm, -3.24 mv respectively. The solubility studies proven the nanosuspension shows more solubility than pure drug. The Powder X-ray Diffraction (PXRD) results indicates that the drug exists as unchanged crystalline nature which improved the solubility by media milling technique. Further, the suspension was converted to oral disintegration tablets and evaluated. The results shows that in vitro release of disintegrating tablets with ludipress with more than 85% drug release than formulations with kollidon, Croscarmellose sodium. Conclusion: From the result it may be concluded that the formulated oral disintegrated tablet with uniform sized stable nanosuspension showed enhanced dissolution which may lead to enhanced oral bioavailability of Lurasidone HCl.